“Real Sexual Harassment”: Attrition Among Police-Reported Sexual Molestation Crimes in Sweden - Wegerstad, Linnea; Andersson, Ulrika (Violence Against Women, 2025)
This article presents findings from a quantitative analysis of 215 case files regarding incidents of the crime of sexual molestation reported to the Swedish Police. We track the incidents through the criminal justice system and show a clearance rate of 9%. The clearance rate is higher when the attack is of a physical nature, the suspect is a stranger, and the incident occurs in a public place. While the statutory definition of sexual molestation is inclusive, this study shows that substantially there is a typical case of sexual harassment that is criminalized; a kind of “real sexual harassment” emerges.
Keywords: Förundersökningar; Sexuellt våld; Kriminalisering; Attrition; Sexuellt ofredande; Straffrätt; Preliminary investigations; Sexual violence; Criminalization; Attrition; Sexual harassment; Criminal law